Influence of B2O3 incorporation on the structural, mechanical and radiation shielding properties of TeO2 Based bioglasses - Ulas, Esmanur Oruc; Acikgoz, Abuzer; Aktas, Bulent; Kavun, Yusuf (Applied radiation and isotopes, 2025)
This study investigates the structural, mechanical, and radiation shielding properties of a series of novel bio glasses with the composition (55-x)TeO2-20Na2O-10CaO-15P2O5-xB2O3 (where x = 0, 3, 5, 10, and 20 mol%). The aim was to evaluate the effect of B2O3 addition on these properties. Empirical methods were used for calculating the mechanical and elastic properties. XRD analysis confirmed the amorphous nature of the glasses, while FTIR spectroscopy revealed the presence of characteristic functional groups associated with TeO2 and B2O3. The results indicate that B2O3 incorporation significantly reduces the glass density (from 4.24 g/cm3 to 3.18 g/cm3) and enhances molar volume (from 29.963 cm3/mol to 34.302 cm3/mol), leading to a less compact glass structure. The mechanical properties were also affected, with fracture toughness decreasing (from 1.367 MPa m1/2 to 1.280 MPa m1/2) and hardness increasing (from 3.091 GPa to 3.207 GPa). Regarding radiation shielding performance, the Linear Attenuation Coefficient (LAC) values decreased with increasing B2O3 content, indicating a deterioration in shielding effectiveness due to the lower effective atomic number of B2O3 compared to TeO2. These findings demonstrate that while B2O3 improves mechanical hardness and molar volume, it compromises radiation shielding properties by reducing glass density and attenuation capacity. •Bioactive glasses with (55-x)TeO2-20Na2O-10CaO-15P2O5-xB2O3 were studied for x values from 0 to 20 %.•XRD confirmed an amorphous structure; density decreased from 4.24 g/cm3 to 3.18 g/cm3 with increasing B2O3.•Fracture toughness decreased (1.367–1.280 MPa m0.5), while hardness increased (3.091–3.207 GPa).•LAC and MAC values decreased as B2O3 content increased consistent across empirical measurements and theoretical calculations.